Intervention Policies and Market Integration: A Case of the Rice Markets in Bangladesh - Ahmad Mostafi, Bazlul Ameen (1993)
Rice plays an important role in the economy of Bangladesh. However,the current poor state of the rice sector is of great concern to the government.The efficient functioning of the marketing system is severely constrained by the role of the beneficiaries. The consequences are-high marketing margin and price instability. Any attempt at seeking appropriate measures to be adopted in order to achieve and sustain a coherent and comprehensive marketing system calls for an indepth study of two major aspects; the effects and implication of the government intervention on the rice market and the nature of integration and price relationship among the various rice markets in the country. The focus of this thesis lies on these two important issues related to rice markets in Bangladesh. A standard partial equilibrium approach was carried out to measure the effects of the government intervention on the rice market. Various parameters such as welfare gain of the producers and consumers, changes in the government revenues and foreign exchange bill were estimate. The results indicated that from the existing policy regimes, the benefit of government intervention mostly went to the consumers. Moreover, the measures could not provide enough incentive to the producers towards enhanced food grain production. Secondary data covering the period from 1972 to 1987 were used to assess the degree and the nature of market integration between the central market and the other nine district level rice markets. Analysis by correlation method reflects the strong association among the rice markets. The results obtained from the Ravallion approach indicate that the central market price exhibits price leadership over the other local markets. The hypotheses of the long run integration and the absence of the local market characteristics were accepted while those of short run integration and market segmentation were rejected. Granger causality test indicated the existence of unidirectional and instantaneous relation of the central market with the local ones. In order to increase the efficiency of rice markets of Bangladesh, the government should consider the above findings as realistic guidelines to ensure factors such as attainment of a high level of coordination among the production and consumption centres, effective price monitoring in the central market, improvement of communication facilities at the source of price information, availability of market information to the trading sectors and liberalization of the present regulations of the holding of rice stocks.